Student's Literacy and Numeracy Skills in ombok Island, West Nusa Tenggara : Baseline Survey Innovation Based Gender Equality, Disability, and Social - Lukman, Lukman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to analyze the literacy and numeracy skills of students in ombok Island, West Nusa Tenggara based on gender, disability and social equality. The research approach uses a Mixed Method between qualitative and quantitative research with a survey method (cross-sectional). Data collection was carried out involving 2639 respondents from SD and MI students, school principals, teachers, parents, village representatives, and from TTIs. Survey data were obtained through questionnaires, document recording, and interviews. Furthermore, the data were analyzed qualitatively. This study's results show the lowest achievement is the numeration of female respondents in East Lombok Regency, 59.41. Achievements in the same aspect for Central Lombok Regency were higher, namely 62.97. For literacy skills, female respondents in Central Lombok also obtained a higher average (68.91) than female respondents in East Lombok Regency (66.93). The achievement of male respondents in Central Lombok Regency for literacy (69.08) looks lower than male respondents in East Lombok Regency (69.44). The same thing also happened to the average achievement in the numeracy aspect; Central Lombok Regency only got an average of 66.00, while East Lombok reached 66.44. In general, male literacy achievements were higher than women, while numeracy achievements were superior to female respondents from men's.